Evaluation of Aflatoxin B1 and Patulinin Blood of Iraqi Renal Failure patients (Medico Legal Update, 2021)
Objectives: The current study aimed to investigate and evaluatethe Aflatoxin B1 and Patulin in bloodsamples of patients with Renal Failure.Method: Hundred fifty blood samples collected from patients with Renal Failure were included in thisstudy. The agerange of patients was 1-61 years. Toxin extraction from the samples was done by Thin LayerChromatography technique (TLC).Results: There were 100 from 150 samples of blood containedAflatoxinB1and Patulin. The highestpercentage blood samples contamination with Aflatoxin B1 was (18.181 %) at age group (11-30) years andPatulin was (20 %) that collected from persons at age group (11-20) years,the percentage of blood samplesthat contamination withAflatoxin B1 and Patulin that collected from the female was (52.727 % and 53.33%).Conclusion: Persons in Najaf province high exposure to mycotoxins from foods (apples,pear and peach)that present in local markets, that are contaminated with mycotoxins. This suggests that these mycotoxinsmay be a risk factor of renal failure.